Effects of High Temperature Stress on Leaf Chlorophyll Fluorescence Characteristics of Kiwifruit - Li Hualong; Wang Jinghong; Zhang Weimin; Bai Qinfeng; Zhang Tao; Pan Yuying; Quan Wenting (应用气象学报)
Kiwifruit is a vine with poor resistance to high temperature. The original habitat is mostly semi shade environment under mountain forest, with humid air, mild temperature change and weak light. The main problem in production is that the temperature of tree is often too high when the tree is introduced from the original forest environment in mountainous areas to cultivated under the direct sunlight in farmland. The leaves, fruits and trunks often get damaged.With the background of climate warming, in Shaanxi, the main kiwifruit producing area, extreme high temperature weather with daily maximum temperature over 40 ℃ often occurs. The high temperature damage of kiwifruit is particularly prominent, such as leaf wilting, shedding, fruit sunburn, fruit drop, and even tree death.In order to explore the effects of high temperature stress on photosynthetic apparatus of kiwifruit leaves and establish a heat injury identification index based on chlorophyll fluorescence response, the variation characteristics of the FO(minimal recorded fluorescence intensity), Fm(maximal recorded fluorescence intensity), Fa(maximal photochemistry efficiency), ΔWK(relative variable fluorescence difference at 300 μs), Tr(trapped energy flux per area at t=0), Et(electron transport flux per area at t=0), Dd(dissipated energy flux per area at t=0), Rm (density of QA-reducing PSⅡ reaction centers) in kiwifruit leaves under 30 ℃, 33 ℃, 36 ℃, 39 ℃, 42 ℃, 45 ℃, 48 ℃, 50 ℃, 52 ℃, 54 ℃ condition are studied by using the technique of fast chlorophyll fluorescence induction dynamics analysis(JIP-test). The results show that Tr, Rm and ΔWK are all affected by temperature stress in the range of 30-54 ℃, which belongs to PSⅡ sensitive site parameters, in which Tr, Rm show a linear downward trend with the increase of stress temperature, while ΔWK shows an exponential upward trend with the increase of stress temperature. FO, Fm, Fa, Dd, Et show stable or less variable under lower temperature stress, and intensified under higher temperature stress, which belongs to the secondary sensitive site parameters of PSⅡ. Most chlorophyll fluorescence parameters have two mutation critical points at 39 ℃ and 45 ℃. The results show that kiwifruit leaves have mild temperature stress at 30 ℃ ≤ T < 39 ℃, moderate temperature stress at 39 ℃ ≤ T < 45 ℃, and severe temperature stress at T ≥ 45 ℃.